Efektivitas Pembuatan Vlog dalam Pemenuhan Tugas Berbasis Project Based Learning (PJBL) pada Mata Kuliah Rias Fantasi untuk Meningkatkan Softskill Mahasiswa - Sofia Daniati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effectiveness of using vlogs as a Project Based Learning (PBL) media in the Fantasy Makeup course to enhance students’ soft skills, particularly in communication, public speaking, creativity, and problem solving. This research employed a pre-experimental design with a one group pre-test and post-test design. The sample consisted of 25 students selected through a census sampling technique, in which the entire population was used as the research sample. Data were collected through observation and questionnaires administered in two stages: a pre-test before the implementation of the learning model and a post-test afterward. The data were analyzed using a Paired Sample T-Test to identify the mean differences in students’ soft skill scores before and after the learning treatment. The results showed a significant improvement in communication, public speaking, creativity, and problem-solving abilities after the implementation of the vlog-based PBL model. Therefore, the use of vlogs is proven to be an effective and innovative learning medium to strengthen students’ soft skills in the context of the Fantasy Makeup course.